Amino acid profiles and growth performance of spiny lobster Panulirus ornatus fed on combination of three mollusk meals - Kurnia, Agus; Muskita, Wellem Henrik; Hamzah, Muhaimin; Abidin, Laode Baytul; Ruslaini, Ruslaini; Suaida, Suaida; Amanda, Rahel (Aceh Journal of Animal Science, 2024)
Spiny lobster is an economically important marine fish commodity that has a high price and one of the important protein source for people worldwide. The quality of the protein is strongly depending on the amino acid compositions and concentrations. This study aimed to determine of amino acid profiles and growth of spiny lobster (Panulirus ornatus) fed with the diet contained combination of three mollusk meal. Four experimental diets were prepared to contain of 40% fish meal,FM (Diet A), 15% telescopium meal, + 15% gold snail meal + 10% scallops meal (Diet B), 15% telescopium meal + 10% gold snail meal + 15% scallops meal (Diet C), 10% telescopium meal + 15% gold snail meal + 15% scallops meal (Diet D) in the test diet. A total of 36 spiny lobster juvenile (initial weight : 120 15,38 g) were distributed into twelve plastic tanks (three lobster/ tank ) with sized of 605050 cm. Feeding the lobster two times a day (08.00 a.m and 05.00 p.m) in dosage of 8% total biomass weight for 60 days of rearing period. The experiment was designed by using completely randomized design with four treatments and three replications. Collecting data included of weight gain, survival rate, and amino acid content in the fish body. The results showed that feeding the lobster with different feed test was significantly different in weight gain of spiny lobster. The weight gain of spiny lobster fed with combination of mollusk meal had higher than the feed contain fish meal. The highest amount level of amino acid in the lobster body was leucine , while the lowest one was tryptophan. The types and total number of some amino acid profiles in the fish body was similarly with amino acid profile in the diets which contained mollusk meal. This study concluded that the amino acid profiles in the diet contained mollusk meal were suitable for requirement to improve the growth of spiny lobster.